Effect of Localized Mechanical Indentation on Skin Water Content Evaluated Using OCT - Abhijit A. Gurjarpadhye; William C. Vogt; Yajing Liu; Christopher G. Rylander (International Journal of Biomedical Imaging)
The highly disordered refractive index distribution in skin causes multiple scattering of incident light and limits optical imaging and therapeutic depth. We hypothesize that localized mechanical compression reduces scattering by expulsing unbound water from the dermal collagen matrix, increasing protein concentration and decreasing the number of index mismatch interfaces between tissue constituents. A swept-source optical coherence tomography (OCT) system was used to assess changes in thickness and group refractive index in ex vivo porcine skin, as well as changes in signal intensity profile when imaging in vivo human skin. Compression of ex vivo porcine skin resulted in an effective strain of −58.5%, an increase in refractive index from 1.39 to 1.50, and a decrease in water volume fraction from 0.66 to 0.20. In vivo OCT signal intensity increased by 1.5 dB at a depth of 1 mm, possibly due to transport of water away from the compressed regions. These finding suggest that local compression could be used to enhance light-based diagnostic and therapeutic techniques.